37.6k views
3 votes
Does anyone know??

i need help like really bad

Does anyone know?? i need help like really bad-example-1

1 Answer

2 votes

Answer:

Down below :#

Explanation:

The first one is False: reason
\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c)


b^9b^2=b^(9+2)


=b^(9+2)

And then its b^11

Second one is false

Third one is True

Fourth false

Reason:
\mathrm{Apply\:exponent\:rule:\:}\left(a^b\right)^c=a^(bc),\:\quad \mathrm{\:assuming\:}a\ge 0


=b^(6\cdot \:5)

fifth one is False


\mathrm{Apply\:exponent\:rule:\:}a^0=1,\:\quad \mathrm{\:assuming\:}a\\e \:0

That equals 1

:) hope this helps

User Bpirvu
by
5.0k points